CONCEPTUAL METAPHORS IN ENGLISH AND UZBEK MOBILE COMMUNICATION TERMINOLOGY: A COGNITIVE-COMPARATIVE STUDY - Arzimurodova Ezoza (International Journal of Literature and Language Studies, 2026)
The rapid expansion of mobile communication technologies has significantly influenced the lexical systems of modern languages, particularly through the emergence of metaphorically motivated terminology. This study investigates conceptual metaphors in English and Uzbek mobile communication terminology from a cognitive-comparative perspective. Drawing upon Conceptual Metaphor Theory proposed by Lakoff and Johnson, the research examines how abstract technological concepts are understood through concrete human experience. The study employs comparative-linguistic, semantic, cognitive, and terminological analysis methods to identify dominant conceptual metaphor models and determine their structural and semantic characteristics in both languages. The findings reveal that the most productive metaphorical domains include SPACE, MOVEMENT, HUMAN BODY and WAR metaphors. English terminology demonstrates higher metaphorical productivity and innovation, whereas Uzbek terminology predominantly adapts English conceptual structures through borrowing, semantic calquing, and partial localization. The research contributes to cognitive linguistics, comparative terminology studies, and the development of Uzbek ICT lexicography by providing one of the first systematic analyses of conceptual metaphors in English and Uzbek mobile communication terminology.